Amino functionalized Zn/Cd-metal–organic frameworks for selective CO2 adsorption and Knoevenagel condensation reactions. Issue 12 (7th March 2019) - Zhai, Zhi-Wei; Yang, Shuang-Hua; Lv, Ya-Ru; Du, Chen-Xia; Li, Lin-Ke; Zang, Shuang-Quan
Abstract : Two amino functionalized Zn/Cd-MOFs can be employed to adsorb CO2 selectively and to catalyze Knoevenagel reactions under solvent-free conditions. Abstract : Two amino functionalized Metal–Organic Frameworks (MOFs), {[Zn(Py2 TTz)(2-NH2 -BDC)]·(DMF)} n (1 ) and {[Cd(Py2 TTz)(2-NH2 -BDC)]·(DMF)·0.5(H2 O)} n (2 ) (where Py2 TTz = 2, 5-bis(4-pyridyl)thiazolo[5, 4- d ]thiazole, 2-NH2 -BDC = 2-amino-1, 4-benzenedicarboxylate, and DMF = N, N -dimethylformamide), were synthesized and characterized using the primary ligand 2-amino-1, 4-benzenedicarboxylic acid (2-NH2 -H2 BDC) and the auxiliary ligand 2, 5-bis(4-pyridyl)thiazolo[5, 4- d ]thiazole (Py2 TTz). They possess similar 2-fold interpenetrated three-dimensional bipillared-layer framework structures composed of typical binuclear metal nodes, 2-NH2 -BDC two-dimensional layers and Py2 TTz bipillars. Notably, thiazole nitrogen atoms and pendant –NH2 groups are present in channels in the two frameworks. Given their good chemical stabilities, high thermal stabilities, and exposed nitrogen sites, gas adsorption and catalytic experiments of the two MOFs were performed. The results demonstrate that MOF2 can selectively adsorb carbon dioxide gas; moreover, the two MOFs can be employed as recyclable heterogeneous catalysts for Knoevenagel condensation reactions under solvent-free conditions.